2020
DOI: 10.1136/bmjopen-2019-034459
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of integrated operating rooms: how much time is saved and how do medical staff experience the upgrading? A mixed methods study in Denmark

Abstract: ObjectivesTo evaluate staff experiences of the implementation and use of integrated operating rooms (IORs) in comparison to conventional operating rooms (CORs) in Denmark.DesignThis study used a mixed methods approach by combining quantitative (registry-based analysis of surgical time) and qualitative (interviews with experienced surgical staff) perspectives.SettingHospitals in Denmark.MethodsThe quantitative component compared the time consumption of patients between the integrated and CORs in two hospital de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The amalgamation of the gadgets enhanced safety, greater confidence, accuracy, and tissue respect in open surgeries, minimally invasive surgeries, and complex cases. IOTSS helps in improving the capabilities of the surgeons and surgical team and ensures a safe environment for the patient [3]. It increases surgeon confidence and expands the horizon of complex cases.…”
Section: Integrated Operation Theater Spine Suite-enablingmentioning
confidence: 99%
See 1 more Smart Citation
“…The amalgamation of the gadgets enhanced safety, greater confidence, accuracy, and tissue respect in open surgeries, minimally invasive surgeries, and complex cases. IOTSS helps in improving the capabilities of the surgeons and surgical team and ensures a safe environment for the patient [3]. It increases surgeon confidence and expands the horizon of complex cases.…”
Section: Integrated Operation Theater Spine Suite-enablingmentioning
confidence: 99%
“…Any deviation from normal anatomy, making the surgeon opt for the best possible surgical plan. This technology benefits complex spine deformities such as ky phoscoliosis, craniovertebral junction, revision surgeries, and minimally invasive surgeries [3]. The chance of getting a C.T.…”
Section: Integrated Operation Theater Spine Suite-enablingmentioning
confidence: 99%
“…Given the merits of both uniportal VATS under non-intubated anesthesia and ENB, the concept of the integrated operating room was appeared and developed. Previous studies ( 8 11 ) have found that the integrated operating room could reduce the interruption in the operation process, optimize the workflow. Thus, it was less time-consuming and potentially improved safety in the OR.…”
Section: Introductionmentioning
confidence: 99%